2016
DOI: 10.1111/pbr.12364
|View full text |Cite
|
Sign up to set email alerts
|

Application of marker‐assisted backcross to introgress Bph3, Bph14 and Bph15 into an elite indica rice variety for improving its resistance to brown planthopper

Abstract: To improve brown planthopper (Nilaparvata lugens St al; BPH) resistance of an elite indica cultivar of South China, Hemeizhan (HMZ), we applied marker-assisted backcross (MABC) to incorporate three BPHresistance genes (Bph3, Bph14 and Bph15) into the genetic background of HMZ. In the third backcross (BC 3 ) generation, we obtained near-isogenic lines (Bph3-NIL, Bph14-NIL, Bph15-NIL and Bph14 + Bph15-NIL) with more than 96% recovery of recurrent parent genome, and pyramided lines (Bph3 + Bph14-PYL, Bph3 + Bph15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…The results indicated that the severity scores of rice lines were RHT<BPh68S<Lianyou8676<Fuhui676< TN1 (Figure 1). RHT scored 0.4 in this study, exhibited a high resistance (HR) to BPH, and fitted well with the findings of Li et al (2011) [36] and Hu et al (2016) [29], but differed from that of moderately resistant reported by Qiu et al (2011) [37] and Chen et al…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results indicated that the severity scores of rice lines were RHT<BPh68S<Lianyou8676<Fuhui676< TN1 (Figure 1). RHT scored 0.4 in this study, exhibited a high resistance (HR) to BPH, and fitted well with the findings of Li et al (2011) [36] and Hu et al (2016) [29], but differed from that of moderately resistant reported by Qiu et al (2011) [37] and Chen et al…”
Section: Discussionsupporting
confidence: 88%
“…The average resistance score of each line was calculated as the weighted average of the scores for all the seedlings tested. Based on the resistance level evaluation standard of Hu et al (2016) [29], the rice lines were classified as highly resistant(HR), resistant(R), moderately resistant(MR), moderately susceptible(MS), susceptible(S), and highly susceptible(HS) corresponding to 0-0.9, 1.0-2.9, 3.0-4.9, 5.0-6.9, 7.0-8.9, and 9, respectively.…”
Section: Evaluation Of Resistance and Host Choice Of Rice To Bphmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the success of host plant resistance is limited by herbivore adaptation to resistant varieties (often referred to as ‘virulence adaptation’), there has been a clear focus on selecting recognized ‘broad spectrum’ genes/loci, or on pyramiding a number of genes/loci into a single genotype to prolong resistance durability ( Myint et al, 2012 ; Wang et al, 2017 ; Horgan et al, 2018a ). A number of research groups have now developed multiple near-isogenic rice lines with a range of different resistance genes either singly introgressed (monogenic) or pyramided (polygenic) into high-yielding varieties, each with >85% recovery of the recurrent parent genes ( Fujita et al, 2010 ; Hu et al, 2016b ; Jena et al, 2017 ). Polygenic resistance to herbivores is predicted to be stronger ( Fujita et al, 2010 ; Hu et al, 2013 ; Asano et al, 2015 ), have a broader spectrum ( Hu et al, 2016b ; Fan et al, 2017 ), have greater stability ( Ali et al, 2006 ), and be more durable ( Myint et al, 2012 ; Wang et al, 2017 ; Horgan et al, 2018a ) than monogenic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research groups have now developed multiple near-isogenic rice lines with a range of different resistance genes either singly introgressed (monogenic) or pyramided (polygenic) into high-yielding varieties, each with >85% recovery of the recurrent parent genes ( Fujita et al, 2010 ; Hu et al, 2016b ; Jena et al, 2017 ). Polygenic resistance to herbivores is predicted to be stronger ( Fujita et al, 2010 ; Hu et al, 2013 ; Asano et al, 2015 ), have a broader spectrum ( Hu et al, 2016b ; Fan et al, 2017 ), have greater stability ( Ali et al, 2006 ), and be more durable ( Myint et al, 2012 ; Wang et al, 2017 ; Horgan et al, 2018a ) than monogenic resistance. Ecological theory suggests that strong resistance is also likely to have associated costs as plants must balance growth, reproduction and defence (including maintenance) to achieve optimal life-history strategies in their respective niches ( Herms and Mattson, 1992 ; Horgan et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%